Development of multilingual social media data corpus for sentiment classification - Rumaisa, Fitrah; Basiron, Halizah; Saaya, Zurina (Institute of Advanced Scientific Research, Inc., 2019)
The purpose of this study is to develop a corpus, which consists of 2 (two) languages: Bahasa Indonesia and Bahasa Melayu. In both languages, there are several similar vocabularies but have different meanings. The data used on this corpus, taken from social media that is Twitter and Facebook. Each language has 2100 words collected. After manual selection of words, there are 300 vocabularies that have different meanings. The words will be formed into the core of the formed corpus, regardless of the remaining words. This corpus will density on the polarity of each word per language type using automatic-annotation. So that will be formed two corpuses namely Bahasa Indonesia and Bahasa Melayu. This Corpus will be used in subsequent research on sentence-level annotation and demonstrated using manual annotations using human annotators.